Atomic-scale observation of strain-induced local amorphization in face-centered cubic metals. (15th April 2022) - Wang, Zhanxin; Chen, Nianke; Li, Xianbin; Teng, Jiao; Guo, Yizhong; Fu, Libo; Zhang, Zihao; Ma, Evan; Wang, Lihua; Zhang, Ze; Han, Xiaodong
Abstract: The formation of metallic glass through melt processing proves to be the most challenging for pure monatomic face-centered cubic (FCC) metals. Though it has long been conjectured that amorphous monatomic metals can be generated through deforming a solid at room temperature, there is rarely direct evidence to prove that is indeed the case. In this study, mechanical loading was applied to nanometer-sized crystals inside an aberration-corrected transmission electron microscopy, and atomic-scale in situ evidence is provided of strain-induced amorphization in Pt and Ni near room temperature. The loading was applied in such a way that the stress state is complicated, and the strain distribution is non-uniform, restricting dislocation activities in accommodating the imposed strain. The local lattice distortion is then rendered so large and the associated strain energy is so high that the crystal collapses into the amorphous state. As such, even elemental FCC metals can be forced to become amorphous. Graphic abstract: Image, graphical abstract